Pengaruh Kualitas Produk, Harga dan Citra Merek Terhadap Minat Beli Ulang Pelanggan pada PT. Sumber Mas Indah Plywood Bagian Lokal - Lestari, Dian Ayu; Surianto, Moh. Agung (VISA: Journal of Vision and Ideas, 2024)
The objective of this research is to determine how Product Quality, Price, and Brand Image influence Customer Repurchase Intention at PT. Sumber Mas Indah Plywood Local Division. This study employs a quantitative research method, which can be understood as a method used to investigate a specific population or sample, with data collection using research instruments, and data analysis being statistical in nature, aimed at testing predetermined hypotheses. The sample size in this study is 140 people. The sampling technique used is purposive sampling. The results of the study indicate that Product Quality does not affect Customer Repurchase Intention at PT. Sumber Mas Indah Plywood Local Division, whereas Price and Brand Image have an influence on Customer Repurchase Intention at PT. Sumber Mas Indah Plywood Local Division.